Formation and characteristics of reaction intermediates in the solid products from cellulose pyrolysis - Liu, Dawei (Curtin University, 2014)
The thesis provides some new insights into the pyrolysis mechanism of cellulose as a model compound of lignocellulosic biomass, focusing more on the formation and characterisation of the reaction intermediates as important precursors of volatiles produced from cellulose pyrolysis. The formation and characteristics of reaction intermediates largely depend on cellulose properties and pyrolysis conditions. The alkali and alkaline earth metal species also significantly affect the formation and characteristics of reaction intermediates from cellulose pyrolysis.